Augmenting Human Appearance Through Technological Design Layers - Genç, Çağlar; Raudanjoki, Özge; Colley, Ashley; Häkkilä, Jonna (Frontiers in Computer Science, 2022)
Augmenting human appearance with the means of technology can focus on different layers attached or around the body. In this paper, we present a categorization of human appearance and expression, with augmenting skin & its appendages, clothing & textile, accessories, body parts, and digital aura around the body. We report a non-systematic review of related works in each category and discuss their means in expressing functional, hedonic and social aspects. All in all, our work contributes design perspectives of augmenting human appearances and reveals challenges and opportunities.